2020
DOI: 10.1111/1748-5967.12466
|View full text |Cite
|
Sign up to set email alerts
|

Combined transcriptomic and proteomic analysis of flubendiamide resistance in Plutella xylostella

Abstract: Diamondback moth (DBM), Plutella xylostella, is an important pest of crucifers worldwide. The extensive use of diamide insecticides has led to DBM resistance in the world, and this presents a serious threat to vegetable production. In the present study, transcriptomic and proteomic analyses were combined to investigate the potential flubendiamide-resistance mechanism in DBM. The lab-selected (R h) and field-collected (R b) flubendiamide-resistant lines of P. xylostella with resistance ratios of 1889.92-fold an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…8−14 For example, the diamondback moth, Plutella xylostella Linnaeus (Lepidoptera: Plutellidae), is among the most destructive agricultural pests that have developed severe resistance to multiple classes of insecticide. 15,16 Consequently, there is an urgent need for the identification of efficacious alternatives for pest control.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8−14 For example, the diamondback moth, Plutella xylostella Linnaeus (Lepidoptera: Plutellidae), is among the most destructive agricultural pests that have developed severe resistance to multiple classes of insecticide. 15,16 Consequently, there is an urgent need for the identification of efficacious alternatives for pest control.…”
Section: ■ Introductionmentioning
confidence: 99%
“…With the steady expansion of the global population, the future trajectory of agricultural development is increasingly oriented toward environmentally friendly, efficient, health-conscious, and sustainable practices. , Among the various challenges faced, the menace of pests emerges as a main factor impeding efficient agricultural output and jeopardizing global food security. , While a repertoire of pest-controlling measures, including genetically modified (GM) crops and biopesticides, have been introduced and applied successively, traditional chemical insecticides remain the predominant method employed in modern agriculture to protect and safeguard crops from pests at the current stage. , Nevertheless, the excessive and unregulated use of traditional chemical insecticides often leads to environmental contamination, ecological imbalances, and resistance development among pests. For example, the diamondback moth, Plutella xylostella Linnaeus (Lepidoptera: Plutellidae), is among the most destructive agricultural pests that have developed severe resistance to multiple classes of insecticide. , Consequently, there is an urgent need for the identification of efficacious alternatives for pest control.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the wide application of diamide insecticides and lack of rotation, insects have rapidly developed high resistance to the diamide insecticides by evolving mutations in their RyRs. In some cases, the resistance of agricultural insects, such as Plutella xylostella (diamondback moth, DBM), has increased more than 2000 times 8,9 . The diamide insecticides have also caused some ecological problems, including environmental pollution, toxicity to some aquatic organisms and honeybees 10 .…”
Section: Introductionmentioning
confidence: 99%
“…DBM develops resistance to insecticides very rapidly due to its physiological and biochemical characteristics. At present, DBM has developed resistance to all major classes of insecticides (Arruda et al 2020;Charleston et al 2005;Jing et al 2021;Li et al 2020;Pu et al 2010;Wang et al 2019;Zhao et al 2006). The lack of effective insecticides makes it difficult to prevent and control DBM.…”
Section: Introductionmentioning
confidence: 99%
“…Modified acetylcholinesterase (AChE) phenotype (MACE) caused by a mutation in the ACHE gene (ace2) is strongly involved in the resistance of Myzus persicae (Sulzer) (Homoptera: Aphididae) to pirimicarb (Liu et al 2017). Most studies on the mechanisms underlying resistance in DBM have focused on genetic and physiological changes and have reported that mutation of RYR and detoxification metabolism as the two main causes (He et al 2012;Li et al 2020;Wang et al 2020). Transport protein ABCC2 participates in the resistance of DBM to avermectin and chlorfenapyr (Xu et al 2019).…”
Section: Introductionmentioning
confidence: 99%